Innovative Approaches to Teaching Arabic Vocabulary to Novice Learners - Baharun, Segaf (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2025)
In Islamic boarding schools such as Darullughah Wadda’wah, novice Arabic learners are expected to acquire basic conversational skills within their first three months—an intensive demand that often leads to anxiety and limited vocabulary retention when traditional rote methods are applied. This study explores innovative approaches to enhance Arabic vocabulary acquisition among beginner-level students through gamification, task-based learning, and multimodal input. Using a qualitative case study design, data were collected from 120 first-year students aged 12–16 through classroom observations, interviews, focus group discussions, and document analysis. The findings reveal that integrating interactive and mnemonic-based strategies significantly improved student engagement, motivation, and vocabulary recall. Mnemonic storytelling and contextualized learning tasks allowed learners to associate words with meaningful experiences, thereby reducing cognitive load and enhancing language use in real-life situations. Despite challenges related to classroom management and technological adaptation, the study demonstrates that a balanced integration of traditional and innovative methods can transform vocabulary learning into an engaging and effective process. This research contributes a practical, learner-centered model for Arabic language instruction within immersive educational environments.